ANALISIS POTENSI EKONOMI DI KABUPATEN GIANYAR TAHUN 2016-2020 - Suardaya, Dewa Nyoman Rista; Budhi, Made Kembar Sri (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.06.TAHUN.2024, 2024)
The purpose of this study is to analyze the economic base sector in Gianyar Regency. And to analyze potential sectors in supporting economic growth in Gianyar. The method used to determine the base sector using LQ analysis while in determining the potential sector using MRP analysis. The results show that the results of the calculation of the average LQ in 2016-2020 show that the economic sector in Gianyar Regency is classified in the category of the base sector with the criteria for the LQ calculation value greater than 1, namely there are ten (10) sectors, namely Mining and Quarrying, Manufacturing Industry, Construction, Provision of accommodation and food and drink, Information and Communication, Real Estate, Corporate Services, Government administration, defense and compulsory social security, Health services and social activities, Other services. Meanwhile, the potential sectors are: the mining and quarrying sector, the transportation and warehousing sector, the accommodation and food and drink supply sector. The Gianyar Regency Government needs to establish development policies by prioritizing superior/based sectors in Gianyar Regency while still paying attention to non-based sectors proportionally.